M-Payment and Covid-19: Understanding the Determinants of Consumers Adopting and Recommending Digital Payment System - Anggit Yoebrilianti; Khairul Ikhsan; Nurhayani Nurhayani (University of Merdeka Malang, 2022)
This study aims to analyze the adoption of m-payment in Indonesia during pandemic Covid-19 using the technology acceptance model (TAM) and unified theory of acceptance and use of technology (UTAUT), particularly to examine its impact on intention to recommend. The population in this study is users of digital payment from several applications such as GoPay, OVO, Dana, Linkaja, and Shopeepay. The research sample was taken using purposive sampling technique with a minimum of 125 respondents. A total of 213 questionnaires was obtained from the respondent of m-payment users in Jakarta, Tanggerang, Bandung and Serang. Using PLS-SEM, it is found that usefulness, ease of use, visibility and security affect intention to use m-payment, with relative advantage has no significant effect on intention to use. In addition, intention to recommend m-payment is influenced by intention to use.